Preparedness of islamic boarding school students for earthquakes and tsunamis in Pasie Nan Tigo Padang - Sutrisno, Ananda Prastuti; Topik, Mohamad Ilham; Marita, Zadam (Journal of Midwifery and Nursing, 2025)
Many aspects affect preparedness in adolescents, one of which is the environmental conditions in which the adolescents live, such as Islamic boarding school students who live 100 meters from seashore. Since its establishment, Islamic boarding school has never received any training on earthquake and tsunami preparedness. The purpose of this research was to determine the level of preparedness of Islamic boarding school students to face the earthquakes and tsunamis in Pasie Nan Tigo Padang. This research was descriptive quantitative with a cross sectional research design. The sample in this research were Islamic boarding school students, totaling 86 students used the proportional stratified random sampling' sampling technique and met the criteria. The instrument used questionnaire of LIPI-UNESCO/ISDR (2006). Based on the results, that 60.5% of Islamic boarding school students had a moderate level of preparedness to face with earthquakes and tsunamis. Parameter of knowledge about disaster as many as 61,6% of students in the medium category, parameter of emergency planning as many as 69,8% of students in the low category, parameter of warning system as many as 66,3% of students in the low category, and parameter of resource mobilization capacity as many as 87,2% of students in the low category. It is suggested that Islamic boarding school cooperate with disaster-related agencies to conduct disaster counseling and simulations as well as facilitate existing infrastructure related to disasters.